2006
DOI: 10.1183/09031936.00033106
|View full text |Cite
|
Sign up to set email alerts
|

Naphthoquinone enhances antigen-related airway inflammation in mice

Abstract: ABSTRACT:The current authors have previously demonstrated that diesel exhaust particles (DEP) enhance antigen-related airway inflammation in mice. Furthermore, a recent study has shown that organic chemicals in DEP, rather than their carbonaceous nuclei, are important contributors to the aggravating effects of airway inflammation. However, the components in DEP responsible for the enhancing effects on the model remain to be identified.The current authors investigated the effects of naphthoquinone (NQ), one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 45 publications
2
35
1
2
Order By: Relevance
“…In other studies, 1,2-NQ has been shown to cause the contraction of tracheal smooth muscle in the same concentration range, through activation of the EGFR system (19) leading ultimately to stimulation of the vanillin receptor to cause smooth muscle contraction. In vivo experiments in which 1,2-NQ was intratracheally administered to ovalbumin-sensitized mice resulted in enhanced airway sensitivity and goblet cell hyperplasia, two actions that may indicate airway hyper-responsiveness that is associated with lung disease (12). Because these tissue and whole animal responses are occurring at comparable concentrations, it appears likely that the in vivo effects are mediated by initial inactivation of PTP1B.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, 1,2-NQ has been shown to cause the contraction of tracheal smooth muscle in the same concentration range, through activation of the EGFR system (19) leading ultimately to stimulation of the vanillin receptor to cause smooth muscle contraction. In vivo experiments in which 1,2-NQ was intratracheally administered to ovalbumin-sensitized mice resulted in enhanced airway sensitivity and goblet cell hyperplasia, two actions that may indicate airway hyper-responsiveness that is associated with lung disease (12). Because these tissue and whole animal responses are occurring at comparable concentrations, it appears likely that the in vivo effects are mediated by initial inactivation of PTP1B.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon black ultrafine particles and carbon nanotubes (9,13,14) contain significant concentrations of organic or metallic impurities that can themselves promote pulmonary inflammation (15,16). Diesel exhaust particles consist of a range of particle sizes from the nanoscale up to 10 mm and contain aromatic hydrocarbon contaminants that can directly promote lung inflammation (6,7,17). Titanium dioxide nanoparticles and carbon nanotubes can additionally promote lung inflammation by inducing pulmonary oxidative stress in vivo (13,18).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that carbon black nanoparticles (9)(10)(11), titanium dioxide nanoparticles (12), and carbon nanotubes (13,14) can promote allergic sensitization, allergic airway inflammation (AAI), and/or stimulate dendritic cell (DC) and allergen-specific T cells. However, a significant component of these particle adjuvant effects has been attributed to adsorbed toxic chemicals and metallic impurities and the ability to induce oxidative stress (6,7,13,(15)(16)(17)(18)(19). Notably, information regarding the long-term effects of inert, nontoxic and noninflammatory nanoparticles delivered into the lung on asthma development and pulmonary DC distribution and function is lacking.…”
mentioning
confidence: 99%
“…In particular, exposure to ambient environmental pollutants is known to be associated several allergic symptoms. For example, experimental evidence has shown that exposure to diesel exhaust particles (Inoue et al, 2007;Liu et al, 2008) and phthalate (Yanagisawa et al, 2008) increase allergic responses, and these pollutants have adjuvant activity.…”
Section: Introductionmentioning
confidence: 99%